2015
DOI: 10.1590/0001-3765201520140555
|View full text |Cite
|
Sign up to set email alerts
|

Floristic and structural patterns in South Brazilian coastal grasslands

Abstract: The natural vegetation of Southern Brazil's coastal region includes grasslands formations that are poorly considered in conservation policy, due to the lack of knowledge about these systems. This study reports results from a regional-scale survey of coastal grasslands vegetation along a 536 km gradient on southern Brazil. We sampled 16 sites along the coastal plain with 15 plots (1 m²) per site. All sites were grazed by cattle. We estimated plant species cover, vegetation height, percentage of bare soil, litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
7
1
5
Order By: Relevance
“…In recent years, there have been advances in the floristic knowledge of grassland ecosystems in the region, but studies usually considered single sites or, at best, smaller regions, and have been conducted using different sampling designs and methods (e.g., for Pampa: Caporal & Boldrini, ; Ferreira & Setubal, ; Freitas, Boldrini, Müller, & Verdum, ; Setubal & Boldrini, ; Pinto et al., ; Menezes, Müller, & Overbeck, ; Silva Filho, Macedo, Souza Vieira, & Neves, ; for highland grasslands: Zanin, Longhi‐Wagner, Souza, & Rieper, ; Moro & Carmo, ; Kozera, Kuniyoshi, Galvão, & Curcio, ; Andrade et al., ; Moraes et al., ; Silva, Andrade, Velazco, Galvao, & Carmo, ). These studies are important for describing local floristic patterns and grassland vegetation structure and can be used to describe regional vegetation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been advances in the floristic knowledge of grassland ecosystems in the region, but studies usually considered single sites or, at best, smaller regions, and have been conducted using different sampling designs and methods (e.g., for Pampa: Caporal & Boldrini, ; Ferreira & Setubal, ; Freitas, Boldrini, Müller, & Verdum, ; Setubal & Boldrini, ; Pinto et al., ; Menezes, Müller, & Overbeck, ; Silva Filho, Macedo, Souza Vieira, & Neves, ; for highland grasslands: Zanin, Longhi‐Wagner, Souza, & Rieper, ; Moro & Carmo, ; Kozera, Kuniyoshi, Galvão, & Curcio, ; Andrade et al., ; Moraes et al., ; Silva, Andrade, Velazco, Galvao, & Carmo, ). These studies are important for describing local floristic patterns and grassland vegetation structure and can be used to describe regional vegetation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…(Teixeira et al, 1986); 'restingas' occur in sandy areas and hold mainly xeromorphic arbustive and arboreous plant species and the ground bromeliad Bromelia antiacan- tha Bertol. (Teixeira et al, 1986;Falkenberg, 1999); natural grasslands are dominated by short to medium-sized Poaceae, Asteraceae and Cyperaceae and occur sparsely in sandy areas, specially amidst dunes (Klein et al, 2007;Menezes et al, 2015); lagoons overall have shallow waters with or without periodic seawater discharge and are surrounded by floating macrophytes, occurring as open marshes; oceanic sandy beaches have Pleistocenic and Holocenic origins, plant communities occur in frontal dunes and are composed essentially of Blutaparon portulacoides (A. St.-Hil.…”
Section: Study Areamentioning
confidence: 99%
“…However, further inventories will likely reveal new species for the region. The coast of southern Santa Catarina and Rio Grande do Sul are contiguous and similar in habitat composition (Burger, 1999;Menezes et al, 2015). Some species that occur in the coast of Rio Grande do Sul (Belton, 1994;Bencke et al, 2010) probably also occur in Santa Catarina, but were not found in this state yet due to low densities, inconspicuiness, migratory habits or because they use the region as stopover for only few days.…”
Section: Bird Diversitymentioning
confidence: 99%
“…Estudos sobre a diversidade florística das restingas foram desenvolvidos ao longo dos 5.000 km de extensão do litoral brasileiro (Holzer et al 2004). No entanto, para a Região Sul do país, predominam os levantamentos realizados nos estados do Paraná e Rio Grande do Sul (Menezes et al 2015). Apesar de a faixa litorânea de Santa Catarina (SC) ser extensa, com 29 municípios litorâneos, este Estado possui o menor número de estudos de caracterização florística e estrutural da vegetação de dunas, com apenas nove municípios amostrados (Reitz 1961, Danilevicz et al 1990, Castellani et al 1995, Falkenberg 1999, Klein et al 2007, Menezes et al 2015.…”
Section: Introductionunclassified